PERILAKU PEMBELIAN PRODUK FASHION MEWAH PALSU PADA KONSUMEN DI JAKARTA - Romadhona, Fitria; Sekarkinasih, Annisa A.; Revalina, Revalina; Kurniaty, Dewi (Universitas Jabal Ghafur, 2023)
The flow of globalization makes world development more advanced. this has a positive impact but also a negative impact. One area that has seen an impact from globalization is the fashion industry. The progress of the fashion industry which is getting better and more diverse makes people compete to buy trending products. In addition, globalization has also caused people's lifestyles to change, and they tend to be more consumptive. Primary data was obtained by distributing questionnaires to measure seven variables, namely: integrity, materialism, risk seeking, price-quality inference, self-perception of smart shopper, subjective norm and value awareness of the purchase intention of counterfeit luxury fashion products. This study uses the T-test analysis, with the results showing that the factors that influence the purchase intention of counterfeit luxury fashion products are risk-seeking factors that are positively related to the purchase intention of counterfeit luxury fashion products. This is supported by the dominance of the sample, namely that around 71 people (70.3%) were female and the ages of the respondents mostly ranged from 16-25 years for a total of 95 people (94.1%) who turned out to be the dominant occupation of the respondents as 90 students (98.1%). This is related to the income data of this study, which shows that respondents with no income dominate as many as 37 people (36.6%); the difference is thin with respondents who earn Rp. 1,000,000 - Rp. 2,000,000 as many as 32 people (31.7%), because the dominant respondent is still a student or college student. So, it can be concluded that risk seeking is positively related to the intention to purchase fake luxury fashion products because students have the attitude to be ready to bear the risks that will arise after buying fake luxury fashion products.Keywords: Purchasing; Counterfeit; Luxury Product; Risk Seeking